PENGARUH LATIHAN HATHA YOGA ERHADAP KUALITAS TIDUR PADA LANSIA: EFFECTS OF HATHA YOGA EXERCISE ON SLEEP QUALITY IN THE ELDERLY - Faidah, Nurul; Bindhu, I Putu Bagus Maha; Sriadi, Ni Nyoman Putri (Stikes Wira Medika Bali, 2020)
In elderly aging process many experiencing physical and mental deterioration that can cause various problems such as decreased quality of sleep. One way to improve the quality of sleep in the elderly is to do Hatha Yoga exercises. This study was conducted to determine the effect of Hatha Yoga on sleep quality in elderly. Hatha Yoga is one of the small gymnastics that can be done by elderly aims to cause relaxation effect in order to improve the quality of sleep or improve the quality of sleep to be better. The research design used was pre experimental with One-group Pre test - Post test Design and number of respondents were 20 people. The results showed the quality of sleep before the Hatha Yoga exercise was given the results of the average quality of sleep by 7.10 with a standard deviation of 1.16 and after the Hatha Yoga exercise was obtained the average sleep quality of 3.95 with a standard deviation of 1.31. Based on data analysis using test Wilcoxon Sign Rank Test obtained p value = 0,000 <α (0.05) then Ho rejected and Ha accepted which means there are significant differences in quality of pre and post test bed. Thus, there is an effect of Hatha Yoga exercise on sleep quality in the elderly. Based on the results of the study, it is expected that elderly with poor sleep quality in order to carry out Hatha Yoga exercises regularly and continuously.